Hydrothermal vents as observatories for future ocean acidification (OA) scenarios: an in-situ study to unravel the involvement of ATP binding cassette transporters in the adaptation of marine polychaetes Platynereis spp. to OA - Simonetti, Silvia; Mutemi, Kevin Nzumbi; Romano, Patrizia; Luckenbach, Till; Zupo, Valerio; Gambi, Maria Cristina; Corsi, Ilaria (Frontiers in Marine Science, 2025)
The marine annelid Platynereis dumerilii, is a key model in genetics, evolution, neurobiology, ecology, and ecotoxicology. Along with its sibling species, P. cfr massiliensis, it thrives in both normal and naturally acidified environments. This makes these species ideal candidates for studying mechanisms of tolerance to acidified conditions, resembling future ocean acidification (OA) scenarios. The ATP-binding cassette (ABC) transport proteins help mitigating the adverse impacts of drugs, xenobiotics and physical stressors. There is growing evidence for their involvement to mediate tolerance towards acid-stress in bacteria and tumor cell lines. Such a function may be relevant for the ability of marine species to cope with OA and may be important to consider when predicting future OA scenarios for marine fauna. Here we addressed the question if ABC transporters of Platynereis spp. are involved in compensating adverse effects of low pH by studying ABC transporter transcript levels in marine animals exposed to various pH levels. We firstly examined P. dumerilii whole genome data (version EMBL_pdum_1.0, Genbank assembly: GCA_026936325.1) for the presence of ABC transporter genes, by homology searches, and, using the single-cell atlas database with P. dumerilii gene expression data, we then determined the presence of a potentially relevant subset of ABC transporters from the ABCB, C and G subfamilies in different organs/tissues. Finally, to assess how seawater pH affects ABC transporter expression, we conducted an in-situ reciprocal transplant experiment involving individuals of P. dumerilii/P. cfr massiliensis. Adult specimens were collected inside and outside the CO2 vents off Castello Aragonese (Ischia Island, Italy). Individuals collected from normal pH areas (8.18 ± 0.005) were transplanted to acidified conditions (7.33 ± 0.312), and vice versa, while others were placed in their original areas. We found 81 orthologs from ABC transporter subfamilies A-G, expressed in different organs/tissues including midgut, neurons, body epidermis and ectodermal cells, and somatic and visceral muscle. Following the 30 days transplant experiment, qPCR analyses were performed to examine the expression levels of seven selected genes from the ABCB, ABCC, and ABCG subfamilies (abcb_1, abcb_2, abcb_3, abcc_1, abcc_2, abcc_3, and abcg). Three of these genes were differentially expressed in specimens transplanted from normal pH to low pH areas (abcb_1 and abcg up-regulated while abcb_3 down-regulated). Based on the homology with human ABCB1 and ABCG2, which are crucial in tumor cell adaptation to acidified environments, it seems reasonable to hypothesize that abcb_1, abcb_3 and abcg play a similar role in Platynereis spp. helping in maintaining cellular homeostasis and surviving acid stress.